2018
DOI: 10.55095/achot2018/033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unloading Knee Brace on Dynamic Parameters of the Stance Phase of Gait in Patients with Knee Osteoarthritis

Abstract: PURPOSE OF THE STUDYKnee joint is the most common place where osteoarthritis may occur. A specific therapy is indicated to patients depending on the degree of disability and other signs. The available methods and their clinical value are regularly assessed in systematic reviews and meta-analysis of clinical studies. The evidence of working mechanism of the specific therapeutic intervention is another important part of evaluating its therapy effect. One of the possibilities of knee osteoarthritis conservative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Some studies reported a reduction in pain as early as six weeks after unloading a knee brace in the conservative treatment of KOA [51], compared to usual care, with a positive influence on the dynamics of gait. In fact, in the short-term, knee brace use reflects an increased load on the unaffected limb with a prolongation of the stance phase in both extremities in a long-term effect that persists even after the brace is removed [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported a reduction in pain as early as six weeks after unloading a knee brace in the conservative treatment of KOA [51], compared to usual care, with a positive influence on the dynamics of gait. In fact, in the short-term, knee brace use reflects an increased load on the unaffected limb with a prolongation of the stance phase in both extremities in a long-term effect that persists even after the brace is removed [52,53].…”
Section: Discussionmentioning
confidence: 99%